HUBUNGAN ANTARA KARAKTERISTIK DAN PENGETAHUAN MENGENAI HIPERTENSI DALAM KEHAMILAN DENGAN PERILAKU MENCEGAH KOMPLIKASI HIPERTENSI - Etty Komariah Sambar (LPPM Universitas Bakti Tunas Husada, 2015)
Maternal mortality rate is still high in Indonesia about 359 per 100.000 live births. One of the main causes is hypertension/eclampsia due to complications affected. The purpose of the study was to identify correlation between characteristics and knowledge about hypertension in pregnancy with prevention behaviour of hypertension complication. The study was conducted at RSU Dr. Soekardjo Tasikmalaya in November-Desember 2014. The research method was analitycal descriptive with cross sectional approach. Sampling method was total sampling with 52 respondents. Data collection instrument was questionnaire. Data analysis were univariate, bivariate ( independent t test, Pearson analysis correlation test, Anova one way ) and multivariate multiple regression test. The study showed that respondent’s characteristics that had no relation with prevention behavior of pregnancy complications were mother’s age (p= 0,831), salary (p= 0,069), employment (p= 0,225), parities (p= 0,426), bodyweight increament (p= 0,469), type of pregnancy (p= 0,928) and gestational age (p= 0,310). Variables that had correlation were educational level (p= 0,031) and knowledge (p= 0,032). The most dominant factor in preventing behavior of pregnancy hypertension is educational level (Beta= 0,278). Key words: characteristics, hypertension in pregnancy, knowledge,